Essays in commercial real estate investments - Costa, Odilon Ricardo da Hora Gonçalves Fernandes (2017)
Commercial real estate offers innumerous investment opportunities. Investors, financial institutions and regulators are interested in understanding what are the main determinants of value in real estate markets, measuring appropriate returns and risks related to target assets, and evaluating whether new market trends arising from institutional stakeholders, such as environmental labels, can contribute to property pricing. Differently from other financial asset classes, such as bonds and stocks, commercial buildings have low liquidity, are highly heterogeneous and depreciate over time, limiting their spatial and temporal comparability. Although the financial and economic literature about the industry has evolved significantly in developed economies, quantitative studies remain at embryonic stage in emerging markets. Given the populational and economic growth patterns from the last decades, there is an increasing concentration of emerging market cities among the largest urban agglomerations worldwide, and, consequently, higher demand for commercial properties. The main caveats for the development of quantitative real estate research are the lack of data, concentration of information among large consulting companies, and, in the case of emerging markets, low transparency and reliability in publicly available data. In this context, this research aims at contributing to the real estate literature with unique datasets for the largest office market in Latin America. This thesis is organized in three essays, comprising three distinct research questions surrounding the city of Sao Paulo. The objective of the first essay is to conceptually and empirically assess whether office markets can be viewed as an exclusive niche. The results, based on hedonic theory and regressions, indicate strong segmentation patterns as price formation comes primarily from the microeconomic needs of end users. The study also indicates that backdoor measures adopted by local specialists can be used as a proxy for segmentation when there is limited information on occupiers. The second essay revisits real estate indices available in Brazil and a number of technical and market-specific features which may be useful to improve existing indicators. Moreover, the study develops hedonic indices to highlight how the early recession affected Sao Paulo´s office market. The results show that market dynamics are very specific and emphasize the need for more detailed indicators. The third essay evaluates the relevance of the governance role of voluntary certification schemes based on the signaling literature. The empirical results show that third party audit schemes from internationally accredited institutions can affect real estate values. This essay not only compares labelled and non-labelled buildings, as done by previous studies, but also considers properties that did not obtain certification subsequent to registration.